1. Sprowadź do prostej postaci

a) (2x-1)+ 3x-2 –(4x-6) =
b) 2(3a – 2b )+ 3(4a-2b) – 5 (-a+ b) =
c) (x-3y)(2x+y)=
d) (x+2y)² =
e) ( 4a-2)(4a+2) – (4a-2)² =
f) (x-7)² + (x+ 7)² - (x-7)(x+7) =

2. Rozwiąż równania

a) 8 (3x+2) = 5(6x -4)
b) 3x (x-1) +2 = 3 (x-1)²
c) (x+3)² = x(x -4 )

3. Rozwiąż nierówności

a) 3a-5a-2 ≥ 8a -7 – 9a
b) (x-4)² + 3x ˃ (x+2) (x-2)
c) (2x+3)( 2x-3) – 6x ˃ (2x-1)² -16

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-29T08:17:19+02:00
1. Sprowadź do prostej postaci

a) (2x-1)+ 3x-2 –(4x-6) =2x-1+3x-2-4x+6=x+3
b) 2(3a – 2b )+ 3(4a-2b) – 5 (-a+ b) =6a-4b+12a-6b+5a-5b= 23a-15b
c) (x-3y)(2x+y)=2x²+xy-6xy-3y²= 2x²-5xy-3y²
d) (x+2y)² =x²+4xy+4y²
e) ( 4a-2)(4a+2) – (4a-2)² = 16a²-4-16a²+16a-4= 16a-8
f) (x-7)² + (x+ 7)² - (x-7)(x+7) =x²-14x+49+x²+14x+49-x²+49=x²+147

2. Rozwiąż równania

a) 8 (3x+2) = 5(6x -4)
24x+16=30x-20
24x-30x=-20-16
-6x=-36
x=6
b) 3x (x-1) +2 = 3 (x-1)²
3x²-3x+2=3(x²-2x+1)
3x²-3x+2=3x²-6x+3
-3c+6x=3-2
3x=1
x=1/3
c) (x+3)² = x(x -4 )
x²+6x+9=x²-4x
6x+4x=-9
10x=-9
x=-0,9

3. Rozwiąż nierówności
a) 3a-5a-2 ≥ 8a -7 – 9a
-2a+a ≥ -7+2
-a ≥ -5
a < 5 (tu ma być mniejsze lub równe)
b) (x-4)² + 3x ˃ (x+2) (x-2)
x²-8x+16+3x ˃ x²-4
-5x ˃ -4-16
-5x > -20
x<4
c) (2x+3)( 2x-3) – 6x ˃ (2x-1)² -16
4x²-9-6x > 4x²-4x+1-16
-6x+4x > -15+9
-2x > -6
x < 3